P775 Finger clubbing and Crohn's disease: higher frequency in patients with upper GI lesions in a prospective study. (25th January 2019) - Romeo, S; Neri, B; Lolli, E; Calabrese, E; De Cristofaro, E; Gesuale, C; Biancone, L
Abstract: Background: Finger clubbing (FC) has been associated with Crohn's disease (CD). Clinical relevance of this finding is undefined. Primary aim was, in a prospective single-centre study, to assess if FC is associated with CD severity and behaviour. Methods: From January to December 2016, patients with a diagnosis of CD and detailed clinical records were enrolled. Data expressed as median (range), Chi-squared or T-test as appropriate. Results: FC was assessed in 267 CD patients. Population characteristics were: M 163 (60%), age 47.3 (17–83); age at diagnosis 33.2 (10–82); CD duration 13.3 (1–56). The disease involved ileum (I) in 160 (59.9%); Colon (C) in 12 (4.5%); ileum-colon (I-C) in 69 (25.8%), upper GI in 26 (9.8%) patients. Disease behaviour was non stricturing-non penetrating in 69 (25.8%), stricturing in 137 (51.3%); penetrating in 61 (22.9%) patients. Perianal disease (PA) was observed in 40 (14.9%) patients. Previous surgery in 143 (53.5%); thiopurines use in 113 (42.3%); anti-TNFα use in 99 (37.1%) patients. Smoking habits in CD were recorded (Yes, No, Ex: n = 82 [30.7%], n = 87 [32.5%], n = 98 [36.8%]. Chronic pulmonary diseases were observed in 19 (7.1%). FC was observed in 45/267 (16.8%) patients. In these patients with FC ( n = 45) the lesions involved ileum in 25 (55.6%), colon in 1 (2.2%), I-C in 10 (22.2%), upper GI in 9 (20%). The frequency of upper GI lesions was significantly higher in CD patients with vs. without FC (9/45 [20%] vs. 17/222 [7.7%]; p = 0.01, OR 3.01, CI (95%): 1.2477 to 7.2841). FC was detected in 9/26 (34.6%) patients with upper CD. Other CD lesions were equally distributed in patients with vs. without FC (I: 25/45 [55.6%] vs. 135/222 [60.8%]; p = 0.511; C: 1/45 (2.2%) vs. 11/222 (4.9%); p = 0.419; I-C: 10/45 (22.2) vs. 59/222 (26.6%); p = 0.542. There was no difference between the two groups in terms of conventional immunosuppressive (ISS) nor Anti TNFa therapy (ISS: 21/45 [56.6%] vs. 92/222 [41.4%]; p = 0.58; Anti-TNFa: 20/45 [44.4%] vs. 79/222 [35.6%]; p = 0.26). The frequency of smokers, ex-, no-smokers did not differ between CD patients w/o FC (17/45 [37.8%] vs. 65/222 [29.3%]; p = 0.26; 17/45 [37.8%] vs. 81/222 [36.4%]; p = 0.87; 11/45 [24.4%] vs. 76/222 [34.2%]; p = 0.2. Pneumopaties were recorded in 3/45 (6.6%) with clubbing. Study population characteristics. Finger clubbing prevalence in study population. Conclusions: The prevalence of FC was significantly higher in patients with upper GI lesions. FC in CD patients appeared not related to smoking habits nor to pulmonary diseases.